First Molecular Identification of Three Clinical Isolates of Fungi Causing Mucormycosis in Honduras - Bryan Ortiz; Isis Laínez-Arteaga; Celeste Galindo-Morales; Lilia Acevedo-Almendárez; Kateryn Aguilar; Diana Valladares; Miriam López; Gustavo Fontecha (MDPI AG, 2022)
Mucormycoses are rare but serious opportunistic fungal infections caused by filamentous organisms of the order Mucorales. Here we report the first molecular identification of Rhizopus oryzae (heterotypic synonym Rhizopus arrhizus), R. delemar, and Apophysomyces ossiformis as the etiological agents of three cases of severe mucormycosis in Honduras. Conventional microbiological cultures were carried out, and DNA was extracted from both clinical samples and axenic cultures. The ITS ribosomal region was amplified and sequenced. Molecular tools are suitable strategies for diagnosing and identifying Mucorales in tissues and cultures, especially in middle-income countries lacking routine diagnostic strategies.